Morphology and Release Kinetics of Protein-Loaded Porous Poly(L-Lactic Acid) Spheres Prepared by Freeze-Drying Technique. (15th August 2011) - Sasaki, Takashi; Tanaka, Kazuki; Morino, Daisuke; Sakurai, Kensuke
Abstract : Freeze-drying a biodegradable polymer, poly(L-lactic acid) (PLLA), from 1, 4-dioxane solutions provided very porous spherical particles of ca. 3 mm in radius with specific surface area of 8–13 m 2 g −1 . The surface of the particle was found to be less porous compared with its interior. To apply the freeze-dried PLLA (FDPLLA) to drug delivery system, its morphology and drug releasing kinetics were investigated, bovine serum albumin (BSA) being used as a model drug compound. Immersion of FDPLLA into a BSA aqueous solution gave BSA-loaded FDPLLA, where mass fraction of the adsorbed BSA reached up to 79%. Time-dependent release profile of BSA in water suggested a two-step mechanism: (1) very rapid release of BSA deposited on and near the particle surface, which results in an initial burst, and (2) leaching of BSA from the interior of the particle by the diffusion process. It was suggested that the latter process is largely governed by the surface porosity. The porosity of both the interior and surface was found to decrease remarkably as the concentration of the original PLLA/1, 4-dioxane solution increases, C 0 . Thus, C 0 is a key parameter that controls the loading and releasing of BSA.